Cytokine and Growth Factor Activation In Vivo and In Vitro after Spinal Cord Injury. (23rd June 2016) - Garcia, Elisa; Aguilar-Cevallos, Jorge; Silva-Garcia, Raul; Ibarra, Antonio
Abstract : Spinal cord injury results in a life-disrupting series of deleterious interconnected mechanisms encompassed by the primary and secondary injury. These events are mediated by the upregulation of genes with roles in inflammation, transcription, and signaling proteins. In particular, cytokines and growth factors are signaling proteins that have important roles in the pathophysiology of SCI. The balance between the proinflammatory and anti-inflammatory effects of these molecules plays a critical role in the progression and outcome of the lesion. The excessive inflammatory Th1 and Th17 phenotypes observed after SCI tilt the scale towards a proinflammatory environment, which exacerbates the deleterious mechanisms present after the injury. These mechanisms include the disruption of the spinal cord blood barrier, edema and ion imbalance, in particular intracellular calcium and sodium concentrations, glutamate excitotoxicity, free radicals, and the inflammatory response contributing to the neurodegenerative process which is characterized by demyelination and apoptosis of neuronal tissue.